Specific Features of the Coagulopathy Signature in Severe COVID-19 Pneumonia - Blot, Mathieu; de Maistre, Emmanuel; Bourredjem, Abderrahmane; Quenot, Jean-Pierre; Nguyen, Maxime; Bouhemad, Belaid; Charles, Pierre-Emmanuel; Binquet, Christine; Piroth, Lionel (Frontiers in Medicine, 2021)
Rationale: COVID-19 displays distinct characteristics that suggest a unique pathogenesis. The objective of this study was to compare biomarkers of coagulopathy and outcomes in COVID-19 and non-COVID-19 patients with severe pneumonia. Methods: Thirty-six non-COVID-19 and 27 COVID-19 non-immunocompromised patients with severe pneumonia were prospectively enrolled, most requiring intensive care. Clinical and biological characteristics (including plasma biomarkers of coagulopathy) were compared. Results: At similar baseline severity, COVID-19 patients required mechanical ventilation (MV) for significantly longer than non-COVID-19 patients (p = 0.0049) and more frequently developed venous thrombotic complications (p = 0.031). COVID-19 patients had significantly higher plasma concentrations of soluble VCAM1 (sVCAM1) (5,739 ± 3,293 vs. 3,700 ± 2,124 ng/ml; p = 0.009), but lower levels of D-dimers, vWF-A2, sICAM1, sTREM1, VEGF, and P-selectin, compared to non-COVID-19 patients. Principal component analysis identified two main patterns, with a clear distinction between non-COVID-19 and COVID-19 patients. Multivariable regression analysis confirmed that sVCAM1 rising levels were independently associated with a longer duration of MV. Finally, we identified close correlations between sVCAM1 and some features of COVID-19 immune dysregulation (ie. CXCL10, GM-CSF, and IL-10). Conclusion: We identified specific features of the coagulopathy signature in severe COVID-19 patients, with higher plasma sVCAM1 levels, that were independently associated with the longer duration of mechanical ventilation. Clinical Trial Registration:ClinicalTrials.gov, identifier: NCT03505281.